Isolation and characterization of a novel Rickettsia species (Rickettsia asembonensis sp. nov.) obtained from cat fleas (Ctenocephalides felis) - Maina, Alice N.; Luce-Fedrow, Alison; Omulo, Sylvia; Hang, Jun; Chan, Teik-Chye; Ade, Fredrick; Jima, Dereje D.; Ogola, Eric; Hong, Ge; Breiman, Robert F.; Njenga, Moses K.; Richards, Allen L. (International Journal of Systematic and Evolutionary Microbiology, 2016)
A novel rickettsial agent, ‘Candidatus Rickettsia asembonensis’ strain NMRCiiT, was isolated from cat fleas, Ctenocephalides felis, from Kenya. Genotypic characterization of the new isolate based on sequence analysis of five rickettsial genes, rrs, gltA, ompA, ompB and sca4, indicated that this isolate clustered with Rickettsia felis URRWXCal2. The degree of nucleotide similarity demonstrated that isolate NMRCiiT belongs within the genus Rickettsia and fulfils the criteria for classification as a representative of a novel species. The name Rickettsia asembonensis sp. nov. is proposed, with NMRCiiT (=DSM 100172T=CDC CRIRC RAS001T=ATCC VR-1827T) as the type strain.
Keywords: Ctenocephalides felis; Rickettsia; genotypic characterization